2019
DOI: 10.1021/acs.nanolett.9b02425
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Surface-Enhanced Resonant Raman and Fluorescence Spectroscopy of Monolayer MoSe2: Determination of Ultrafast Decay Rates in Nanometer Dimension

Abstract: The fact that metallic nanostructures are an excellent light receiver and transmitter connects the underlying principles of two widely applied optical processes: surface-enhanced Raman scattering (SERS) and surface-enhanced fluorescence (SEF). A comparative study of SERS and SEF can eliminate the typical unknown quantities of the system and reveal important parameters that cannot be accessed by conventional techniques. Here, we use this simultaneous SERS and SEF technique in a monolayer MoSe 2 coupled plasmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 55 publications
1
59
0
Order By: Relevance
“…The stable biexciton formation in our case is supported by the prior report about resonant excitation of CsPbBr 3 perovskite nanoplate inside the Ag nanowire-Ag film plasmonic nanogaps 53 , which reported that the necessary exciton occupancy for excitation was significantly reduced by~10 6 times from the plasmonic gap. We rule out the possibility of detrimental influence of the Purcell effect on MoSe 2 since plasmonic resonators are well known for large and reproducible enhancement of spontaneous emission 52,[54][55][56] . For example, recent reports on time varying series of tip-enhanced photoluminescence of WSe 2 by repeated engaging and disengaging the tip has proven Purcell enhancement of PL unambiguously.…”
Section: Correlation Of Nanoscale Features Using Tip-enhanced Photolumentioning
confidence: 99%
“…The stable biexciton formation in our case is supported by the prior report about resonant excitation of CsPbBr 3 perovskite nanoplate inside the Ag nanowire-Ag film plasmonic nanogaps 53 , which reported that the necessary exciton occupancy for excitation was significantly reduced by~10 6 times from the plasmonic gap. We rule out the possibility of detrimental influence of the Purcell effect on MoSe 2 since plasmonic resonators are well known for large and reproducible enhancement of spontaneous emission 52,[54][55][56] . For example, recent reports on time varying series of tip-enhanced photoluminescence of WSe 2 by repeated engaging and disengaging the tip has proven Purcell enhancement of PL unambiguously.…”
Section: Correlation Of Nanoscale Features Using Tip-enhanced Photolumentioning
confidence: 99%
“…Second, the chiral particle induces enhanced spontaneous emission, which enables fast depopulation of the valley. [ 29 ] This fast recombination of the excitons reduces the chance that excitons lose the original valley information via intervalley scattering. [ 30 ] Here, we note that our system is not in the strong coupling regime, therefore, the Purcell effect is the expected mechanism.…”
Section: Figurementioning
confidence: 99%
“…The mode splitting phenomenon can be explained by the excitation of a pair of WGMs in clockwise and anti-clockwise directions of propagation when a single scatter is placed on the center of the top or bottom surface of a microsphere. [38][39][40][41] It should be noted that if a microsphere's shape is not regular or there are many defects on the surface, the periodic oscillations and mode splitting phenomena may disappear.…”
Section: Resultsmentioning
confidence: 99%
“…Some groups have recently studied this issue in different pure plasmonic systems. [38][39][40][41][42][43] However, to the best of our knowledge, this issue has been rarely studied in the optoplasmonic system.…”
Section: Introductionmentioning
confidence: 99%